Trained Immunity and its Role in Health and Diseases: A Review - Santosh Kumar Gupta (Indian Journal of Medical Biochemistry)
The term immunity mostly refers to adaptive immunity, even though innate immunity also plays a crucial role. Immunological memory is the key feature distinguishing adaptive immunity from innate immunity. Adaptive immunity features observed in innate cells, i.e., the immunological memory to past insults, has given an entirely new perspective to immunity. This is called trained immunity. Innate cells, after recognition of the pathogens, mount an exaggerated inflammatory response if challenged again. These responses protect not only against the target pathogen but also against other pathogens. This heterologous response of trained immunity is a unique property with a lot of therapeutic promise. Metabolic and epigenetic reprogramming of innate cells are the central mechanisms of trained immunity. This reprogramming, evoked by endogenous and exogenous stimuli, result in trained immunity which is now considered to be evolutionally conserved. It protects the organism in the same way as the adaptive immune memory. Though trained immunity is beneficial, maladaptation at times may lead to hyper-inflammatory state with detrimental effects. Trained immunity has found its applications in understanding many clinical conditions and possibly new therapeutic potential. In this review, a brief account of trained immunity, its mechanistic undercurrents and therapeutic exploitations are described.